Spectral and Biological Studies on New Mixed Ligand Complexes - Pal, T. K.; Alam, M. A.; Hossen, J.; Paul, S.; Ahmad, H.; Sheikh, M. C. (Journal of Scientific Research, 2018)
In this study, new mixed ligand complexes have been prepared from bis(2,4,4-trimethylpentyl)dithiophosphinic acid (C16H35PS2) and 2,9-dimethyl-1,10-phenanthroline (C14H12N2) with various metal(II) ions. The molecular formula of the metal complexes were [Mn(C16H34PS2)(C14H12N2)]Cl (1), [Fe(C16H34PS2)(C14H12N2)]Cl (2), [Co(C16H34PS2) (C14H12N2)]Cl (3), [Zn(C16H34PS2)(C14H12N2)]Cl (4) and [Cd(C16H34PS2)(C14H12N2)]Cl (5). These complexes have been characterized by various physico-chemical techniques such as melting point, molar conductance, magnetic susceptibility measurements as well as UV-Vis, IR, TG and mass spectroscopic analyses. The surface morphology was determined by scanning electron microscope (SEM). The magnetic moment value, color as well as spectral measurements suggested that the geometrical structures of the metal complexes were tetrahedral. The spectral data showed that bis(2,4,4-trimethylpentyl)dithiophosphinic acid and 2,9-dimethyl-1,10-phenanthroline ligands acted as uninegative and neutral bidentate ligand, respectively. The obtained mixed ligand complexes were more stable in air and highly soluble in common organic solvent. The bio-efficacy of ligands and metal complexes have been screened against the test microorganism using agar disc diffusion method. The complex 4 showed potential antibacterial activity against Sterptococcus aureus as compared to standard drug, imipenem. On the other hand, the complex 3 also displayed more potent antifungal activity against Lecanicillium fungicola. Moreover, the complex 3 was also found to have better scavenging activity against 2,2-diphenyl-1-picrylhydrazyl.